Unidirectional ring cavity Raman fiber laser with continuous wave operation for achieving efficient power - Lau K.Y.; Ker P.J. (Alpha Publishers, 2023)
Raman fiber laser in C-band region has undeniable potential in optical communication systems due to the low attenuation at this wavelength band for signal processing and data transmission. Therefore, the extensive investigation for Raman fiber laser in terms of continuous wave and pulse regimes have been sought-after among the engineers and researchers. However, a simple design of the Raman fiber laser is always the merit to minimize the design complexity of the laser system. The main objective of this research work is to propose a simple design of Raman fiber laser which is designed with continuous wave operation. A unidirectional ring laser cavity is tailored by integrating an optical isolator within the Raman fiber laser configuration. The optical spectrum, power development, and the pulse validation for the Raman fiber laser will be thoroughly conducted in this work. The experimental result is expected with the absence of the pulse operation due to the continuous wave laser regime of the proposed Raman fiber laser scheme. The success of this work will contribute to a simple yet flexible design to a C-band Raman fiber laser for optical communication system. 2020 Alpha Publishers.